Reduced Fgf10/Fgfr2 and androgen receptor (AR) in anorectal malformations male rats induced by di-n-butyl phthalate (DBP): A study on the local and systemic toxicology of DBP. (2nd December 2015) - Jiang, Jun-Tao; Xu, Hong-Li; Zhu, Yi-Ping; Wood, Kristofer; Li, En-Hui; Sun, Wen-Lan; Yuan, Quan; Xu, Dong-Liang; Liu, Zhi-Hong; Zhao, Wei; Xia, Shu-Jie
Abstract: Previous study have demonstrated that not only the anorectal development but also the general conditions of anorectal malformations (ARMs) male rats are severely affected by di- n -butyl phthalate (DBP) maternal exposure. However, the mechanisms underlying DBP-induced congenital defects remain elusive. Reportedly, Fgf10/Fgfr2 and androgen receptor (AR) are pivotal for the development of multiple organs. In this study, we therefore investigated the expression of Fgf10/Fgfr2 together with AR in the terminal rectum and multiple organs of ARM male rats induced by in utero exposure to DBP. DBP was administered to pregnant rats to establish the model and the incidence of ARMs in male offspring was 39.5%. On postnatal day(PND)1, the gross photograph and histopathological staining confirmed the abnormal manifestations in these organs of newborn ARMs. Decreased anogenital distance, body weight and serum testosterone level were observed in ARM male offspring. The reduced expression of Fgf10/Fgfr2 mRNA and protein was seen in terminal rectum and kidney, spleen, liver, heart in ARM male rats, whereas the reduced expression of AR was only observed in the kidney and terminal rectum. Our findings suggest the potential involvement of altered Fgf10/Fgfr2 signaling and AR in pathogenesis of local and systemic development defects in ARMs male rats induce by DBP.